Comparison of Anthropometry and Lower Limb Power Qualities According to Different Levels and Ranking Position of Competitive Surfers. Issue 8 (August 2017) - Fernandez-Gamboa, Iosu; Yanci, Javier; Granados, Cristina; Camara, Jesus
Abstract : Abstract: Fernandez-Gamboa, I, Yanci, J, Granados, C, and Camara, J. Comparison of anthropometry and lower limb power qualities according to different levels and ranking position of competitive surfers. J Strength Cond Res 31(8): 2231–2237, 2017—The aim of this study was to compare competitive surfers' lower limb power output depending on their competitive level, and to evaluate the association between competition rankings. Twenty competitive surfers were divided according to the competitive level as follows: international (INT) or national (NAT), and competitive ranking (RANK1–50 or RANK51–100 ). Vertical jump and maximal peak power of the lower limbs were measured. No differences were found between INT and NAT surfers in the anthropometric variables, in the vertical jump, or in lower extremity power; although the NAT group had higher levels on the elasticity index, squat jumps (SJs), and counter movement jumps (CMJs) compared with the INT group. The RANK1–50 group had a lower biceps skinfold ( p < 0.01), lower skinfolds in the legs (Front thigh: p ⩽ 0.05; medial calf: p < 0.01), lower sum of skinfolds ( p ⩽ 0.05), higher SJ ( p < 0.01), CMJ ( p < 0.01), and 15 seconds vertical CMJ ( p ⩽ 0.05); also, maximal peak power of the right leg (MPPR ) and left leg (MPPL ) were higher in the RANK1–50 group. Moderate to large significant correlations were obtained between the surfers' ranking position and some skinfolds, the sum of skinfolds, and vertical jump. Results demonstrate that surfers' physical performance seems to be an accurate indicator of ranking positioning, also revealing that vertical jump capacity and anthropometric variables play an important role in their competitive performance, which may be important when considering their power training.